2016
DOI: 10.1002/asna.201612315
|View full text |Cite
|
Sign up to set email alerts
|

Accretion disc atmospheres and winds in low‐mass X‐ray binaries

Abstract: In the last decade, X-ray spectroscopy has enabled a wealth of discoveries of photoionised absorbers in X-ray binaries. Studies of such accretion disc atmospheres and winds are of fundamental importance to understand accretion processes and possible feedback mechanisms to the environment. In this work, we review the current observational state and theoretical understanding of accretion disc atmospheres and winds in low-mass X-ray binaries, focusing on the wind launching mechanisms and on the dependence on accr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 100 publications
4
76
0
Order By: Relevance
“…Low ionized state plasma, with log ξ ∼ 1.8 − 2.5, has been identified in BH and NS LMXBs in the past (see Table 1 in Díaz Trigo & Boirin 2016). However, we caution that none of these studies included in their models the warmhot component associated to the ISM (but note that van Peet et al (2009) included both a collisionally ionised and a photo-ionised plasma).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low ionized state plasma, with log ξ ∼ 1.8 − 2.5, has been identified in BH and NS LMXBs in the past (see Table 1 in Díaz Trigo & Boirin 2016). However, we caution that none of these studies included in their models the warmhot component associated to the ISM (but note that van Peet et al (2009) included both a collisionally ionised and a photo-ionised plasma).…”
Section: Discussionmentioning
confidence: 99%
“…The crucial question of why the wind is absent during the hard accretion state remains unanswered. Some possibilities include thermal in-E-mail: efraingatuzz@gmail.com stabilities (Chakravorty et al 2013;Bianchi et al 2017), full ionization of the plasma (Ueda et al 2010;Díaz Trigo et al 2012, 2014Díaz Trigo & Boirin 2016), density changes in the wind (Miller et al 2012), geometrical changes in the system (Ueda et al 2010) or mass depletion between winds and jets (Neilsen & Lee 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Strong photoionization can fully ionize a wind, resulting in the disappearance of absorption lines Díaz Trigo & Boirin 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Radio observations of jet outflows have revealed that they are highly collimated, often relativistic, and are launched close to the compact object (Fomalont et al 2001a(Fomalont et al , 2001bFender 2006;Fender & Gallo 2014). Disk winds are typically studied via narrow line features in X-ray spectra; they have a more equatorial geometry, are much slower, and are formed further out (Neilsen 2013;Díaz Trigo & Boirin 2016). Observed behavior in the black hole (BH) LMXB H1743-332 suggested that jets and disk winds are causally related (Miller et al 2006); later, Neilsen & Lee (2009) found that in the BH LMXB GRS 1915+105 the jet outflows are typically quenched when strong disk winds are present (see also Miller et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Bjerkeli et al 2016) through to stellar mass compact objects (both black holes and neutron stars) in X-ray binaries (e.g. Ponti et al 2012;Díaz Trigo & Boirin 2016) and the supermassive black holes in active galactic nuclei (AGN) at the centre of galaxies (e.g. Nardini et al 2015).…”
Section: Introductionmentioning
confidence: 99%